Pedagogical artifact for teaching the theme ’solar energy’: possibilities with the use of recyclable materials - Scabelo, Luciene Galvão; Mendes, Ana Nery Furlan (Brazilian Journal of Production Engineering, 2023)
Faced with the environmental and social challenges of today’s world, renewable energies are gaining prominence as sustainable alternatives. In this context, schools play a fundamental role in promoting awareness and education about these issues. It is from this perspective that this study presents research that aims to explore the topic of solar energy with twenty-eight eighth-year elementary school students. It uses an investigation-based teaching approach, involving experimentation, problematization and hypotheses, to promote the learning of physical-chemical concepts related to solar energy. Furthermore, it employs a didactic sequence divided into three moments: problematization, organization of knowledge and application of knowledge and, as a final development, the creation of a prototype house with a mini solar panel made from recyclable materials. The didactic proposal allowed students to experience the capture of solar radiation and understand concepts of temperature transfer between bodies and heat. Additionally, it encouraged sustainability by exploring the possibility of building residential solar water heaters. The research approach proved to be effective in promoting meaningful student learning, while stimulating environmental awareness and the practical application of knowledge, going beyond the school environment.